A Methodology for Assessing the Performance of Structural Measures to Mitigate Traffic Congestion: A Case Study of Chittagong Port Flyover - Khatun E , Zannat; Showkat, Sanjida; Islam, Md Rabiul (Journal of Bangladesh Institute of Planners, 2014)
An efficient transport system is characterized by accessibility and mobility of traffic works as an impetus for economic development of a country. Chittagong, the business capital of Bangladesh, requires an efficient transport system in order to boost the economic growth. To do so, Chittagong Development Authority has prepared a long term development strategy for traffic and transport system of Chittagong. Some of these strategies include infrastructure development such as flyover, over-pass and expressway construction. But it is necessary to evaluate whether these infrastructures are improving the efficiency of transport system or not. In order to do so, it is also important to identify the major suitable indicators for assessing the performance of those infrastructures for Chittagong. However, Chittagong Port flyover is one of those infrastructures that have already been implemented. The aim of this study is to determine the efficiency of this substantial flyover through the comparison of different suitable roadway and related factors such as Level of Service (LOS), Vehicular Operating Cost (VOC), and Value of Travel time (VOT) etc. before and after the flyover construction. To find out the information, volume survey, speed survey and questionnaire survey have been conducted. It is found that most of the time free flow exists over the flyover and vehicular operating cost reduced for truck. After separating freight transport from passenger carrying traffic, the level of service of the road just beneath the flyover has also improved. It is also found that for assessing the performance this methodology require less survey instrument, less resource and time. This methodology can be used for assessing the performance of other structural measures not only situated in Chittagong but also in any other area of Bangladesh. Journal of Bangladesh Institute of Planners, Vol. 7, Dec 2014, pp. 53-62